THE CORRELATION BETWEEN LEARNING RESOURCES AND STUDENTS’ ENGLISH LEARNING ACHIEVEMENT - Syarif, Dwi Atmawati; Aeni, Nur; Munir, Munir (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2024)
This research aims to determine the relationship between learning resources and students' English learning achievement. This research uses a quantitative approach and correlational methods. The sample in this study was 30 students of class VIII i of SMP Negeri 13 Makassar, and the sample was selected using random sampling technique. Data was obtained from questionnaire answers of 30 respondents and tests of 30 respondents and then correlated. The results of the research concluded that the correlation between learning resources and students' English learning achievement obtained rxy results amounting to 0.376, (between 0.210 - 0.400) where the two variables have a low degree of correlation and a positive form of correlation. It can be concluded that the hypothesis which states that there is a relationship between learning resources and students' English learning achievement is accepted. So, whatever learning resources the teacher uses should be in accordance with the learning objectives so that they can support the student learning process and obtain optimal results.Keywords: Learning Resources, Learning Achievement